Pengembangan Media Edukasi melalui Game Puzzle mengenai Anemia pada Siswa Kelas VIII di SMPN 38 Padang: Development of a Puzzle-Based Educational Game on Anemia among Eighth-Grade Students at SMPN 38 Padang - Aulia, Reghina; Andrafikar, Andrafikar; Hasniyati, Rina; Edmon, Edmon; Umar, Hermita Bus (Jurnal Ilmu Gizi dan Dietetik, 2026)
Anemia remains a prevalent nutritional problem among adolescents, particularly adolescent girls. Based on data from the Padang City Health Office in 2021, the prevalence of anemia among adolescent girls reached 42.5%, increasing to 70.8% in 2023 at SMPN 38 Padang. Inadequate iron intake and low levels of knowledge are among the primary contributing factors to anemia. This study aimed to develop an educational media in the form of a puzzle game about anemia that is valid, feasible, and effective in improving adolescents’ knowledge. This study employed a Research and Development (R&D) design using the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. The study was conducted at SMPN 38 Padang in 2025. The research subject was the developed educational media, while the product trial involved 30 eighth-grade students. Validation was carried out by two material experts and two media experts. The validation results indicated that the media was highly valid, with an average expert validation score of 89.6%. The feasibility test conducted by students showed a very feasible category with an average score of 90.85%. The pretest and posttest results demonstrated an increase in the mean knowledge score from 4.77 to 6.67. The Wilcoxon test showed a significance value of 0.000 (p<0.05), indicating that the puzzle-based educational media was effective in improving students’ knowledge. In conclusion, the puzzle game can be used as an interactive and engaging educational medium for adolescent nutrition education.